2017
DOI: 10.3121/cmr.2017.1349
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Thrombosis in Patients with Antiphospholipid Syndrome Receiving Newer Oral Anticoagulants: A Case Report and Review of Literature

Abstract: We present the case of a patient with primary APS who had a recurrence of thrombotic event while on treatment with rivaroxaban and had to be restarted on warfarin. The current literature on recurrence of thrombotic events in patients with antiphospholipid syndrome (APS) treated with newer oral anticoagulants (NOAC) is also reviewed. Relevant case reports and case series were identified by searching the Medline database using the key words antiphospholipid syndrome, anticoagulants and names of the NOACs, and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Triple positivity (positivity of all three laboratory criteria for APS) was associated with a 3.5-fold increased risk of recurrent thrombosis. 107…”
Section: Neurological Manifestations In Apsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triple positivity (positivity of all three laboratory criteria for APS) was associated with a 3.5-fold increased risk of recurrent thrombosis. 107…”
Section: Neurological Manifestations In Apsmentioning
confidence: 99%
“…Triple positivity (positivity of all three laboratory criteria for APS) was associated with a 3.5-fold increased risk of recurrent thrombosis. 107 The RAPS trial, a randomized controlled, open label non-inferiority trial that compared rivaroxaban with warfarin in APS patients showed that endogenous thrombin potential (ETP) for rivaroxaban did not reach the non-inferiority threshold, but there was no increase in thrombotic risk compared with standard-intensity warfarin. It did not include patients with previous arterial manifestations or with recurrent venous thrombosis while on therapeutic warfarin dose.…”
Section: Management Of Neurologic Thrombotic Manifestationsmentioning
confidence: 99%
“…1,4,5 Until April 2018, 203 patients with APS receiving DOACs, mostly rivaroxaban (86%), along with 17 subjects on dabigatran and 11 cases on apixaban have been reported. 1,413 In a randomized British trial 54 patients treated with 20 mg once daily rivaroxaban were followed for 210 days and no adverse events were observed. 14 Patients with APS who developed VTE on standard-intensity anticoagulation and those following arterial thrombosis (AT) were excluded from this study.…”
Section: Introductionmentioning
confidence: 99%
“…Though unclear at this point, mechanisms of hypercoagulability similar to antiphospholipid syndrome (APS) might have a role to play in thrombosis in COVID-19 patients [ 8 ]. Lately, there has been a debate if DOAC therapy is appropriate in patients with APS as there are published reports of patients with APS who were being treated with a DOAC were found to have recurrent thromboembolic manifestations and had to be switched to Vitamin K antagonists (VKAs) [ 9 ]. This could indicate that the use of DOACs in COVID 19 may not be effective in the prevention of thrombosis in this patient population as there might be a possible role of lupus anticoagulant positivity in hypercoagulation in patients with COVID19.…”
Section: Reviewmentioning
confidence: 99%